2017
DOI: 10.33549/physiolres.933732
|View full text |Cite
|
Sign up to set email alerts
|

Patients With IgA Nephropathy Have Altered Levels of Immunomodulatory C19 Steroids. Glucocorticoid Therapy With Addition of Adrenal Androgens May Be the Choice

Abstract: Glucocorticoid (GC) therapy is one of the methods of choices for treatment of autoimmune diseases (ADs). In addition, adrenal androgens are known as immunoprotective GC-antagonists. Adrenal steroids preferentially influence the Th1-components over the Th2 ones. We investigated steroid metabolome (using gas chromatography-mass spectrometry) in healthy controls (H), GC-untreated patients with ADs different from IgA nephropathy (U), GC-treated patients with ADs different from IgA nephropathy (T) and in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…In these diseases, the CRH operates on both peripheral and central levels [4,5]. The CRH indirectly operates in an anti-inflammatory fashion via the stimulation of anti-inflammatory cortisol and immunoprotective adrenal androgens [6], while the autocrine/paracrine peripheral effect is the opposite [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these diseases, the CRH operates on both peripheral and central levels [4,5]. The CRH indirectly operates in an anti-inflammatory fashion via the stimulation of anti-inflammatory cortisol and immunoprotective adrenal androgens [6], while the autocrine/paracrine peripheral effect is the opposite [7].…”
Section: Introductionmentioning
confidence: 99%
“…The data from the FZ as reported by Siriani et al [13] showed increased mRNA expression of the genes needed for DHEAS production, such as steroidogenic acute regulatory protein, cholesterol desmolase (CYP11A1), steroid C17-hydroxylase-C17,20-lyase (CYP17A1), and type 2A1 steroid sulfotransferase (SULT2A1), as well as the upregulation of type 1 CRH receptors after 24 h treatment of FZ cells with CRH, CRH-related peptide urocortin or ACTH. The various adrenal steroids that have synthesis controlled by CRH and ACTH as well as their metabolites may operate as neuroactive [14], neuroprotective [15] and immunoprotective [6] substances, affecting the somatic, psychosomatic and psychiatric health of patients [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The reduced activity of CYP17A1 C17,20-lyase step in ICP patients might also be associated with an impaired expression of CYB5 enzyme (Rege et al 2016) in the maternal zona reticularis. We have also found attenuated activity of the CYP17A1 C17,20 lyase step in further pathologies such as IgA nephropathy (Sterzl et al 2017), mood and anxiety disorders and Alzheimer's disease (Vankova et al 2016). This insufficiency was sometimes accompanied by reduced sulfotransferase activity (Vankova et al 2015).…”
Section: Labor Daymentioning
confidence: 87%
“…The present GC-MS/MS method includes a wide range of analytes, which reflect activities of most steroidogenic enzymes. Thus, it could be used for the estimation of changes in steroidogenesis for various physiological and pathophysiological situations and subsequently the data obtained can be utilized for uncovering the mechanisms of some steroidrelated human pathologies (Parizek et al 2016, Sterzl et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid profiling helps various pathologies to be rapidly diagnosed. Moreover, the results from analyses investigating steroidogenic pathways may be used as a tool for uncovering pathology causations and proposals of new therapeutic approaches (Bicikova et al 2013, Hill et al 2010c, Kanceva et al 2015, Parizek et al 2016, Sosvorova et al 2015, Sterzl et al 2017.…”
Section: Introductionmentioning
confidence: 99%